ANALISIS PENGARUH PELATIHAN KERJA TERHADAP PRESTASI KERJA KARYAWAN PADA UNIVERSITAS TRUNAJAYA BONTANG - Martopan Abdullah; Kalist Sabbatho (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2019)
Job training is needed so that the quality of the workforce increases. Trunajaya Bontang University in improving work performance is felt necessary to provide job training to staff and lecturers in the campus environment. This study aims to determine the relationship in Job Training to Employee Job Performance at Trunajaya University Bontang. The method of analysis in this study is the validity test, reliability test, Correlation Coefficient, Determination Coefficient, hypothesis testing. From the results of the interpretation of the calculation of the coefficient of determination, obtained value r2 = 0.79 (positive), this shows that 79% of the variation is explained by the positive relationship or influence between the variable "Job Training" with "Employee Job Performance", while the remaining 21% is influenced by other factors. Keywords: Job training, Job performance, staff